Findings from world mental health surveys of the perceived helpfulness of treatment for patients with major depressive disorder (2020)
IMPORTANCE The perceived helpfulness of treatment is an important patient-centered measure that is a joint function of whether treatment professionals are perceived as helpful and whether patients persist in help-seeking after previous unhelpful treatments. OBJECTIVE To examine the prevalence and factors associated with the 2 main components of perceived helpfulness of treatment in a representative sample of individuals with a lifetime history of DSM-IV major depressive disorder (MDD). DESIGN, SETTING, AND PARTICIPANTS This study examined the results of a coordinated series of community epidemiologic surveys of noninstitutionalized adults using theWorld Health OrganizationWorld Mental Health surveys. Seventeen surveys were conducted in 16 countries (8 surveys in high-income countries and 9 in low- and middle-income countries). The dates of data collection ranged from 2002 to 2003 (Lebanon) to 2016 to 2017 (Bulgaria). Participants included those with a lifetime history of treated MDD. Data analyses were conducted from April 2019 to January 2020. Data on socioeconomic characteristics, lifetime comorbid conditions (eg, anxiety and substance use disorders), treatment type, treatment timing, and country income level were collected. MAIN OUTCOMES AND MEASURES Conditional probabilities of helpful treatment after seeing between 1 and 5 professionals; persistence in help-seeking after between 1 and 4 unhelpful treatments; and ever obtaining helpful treatment regardless of number of professionals seen. RESULTS Survey response rates ranged from 50.4%(Poland) to 97.2%(Medellín, Columbia), with a pooled response rate of 68.3%(n = 117 616) across surveys. Mean (SE) age at first depression treatment was 34.8 (0.3) years, and 69.4%were female. Of 2726 people with a lifetime history of treatment of MDD, the cumulative probability (SE) of all respondents pooled across countries of helpful treatment after seeing up to 10 professionals was 93.9% (1.2%), but only 21.5%(3.2%) of patients persisted that long (ie, beyond 9 unhelpful treatments), resulting in 68.2%(1.1%) of patients ever receiving treatment that they perceived as helpful. The probability of perceiving treatment as helpful increased in association with 4 factors: older age at initiating treatment (adjusted odds ratio [AOR], 1.02; 95%CI, 1.01-1.03), higher educational level (low: AOR, 0.48; 95%CI, 0.33-0.70; low-average: AOR, 0.62; 95%CI, 0.44-0.89; high average: AOR, 0.67; 95%CI, 0.49-0.91 vs high educational level), shorter delay in initiating treatment after first onset (AOR, 0.98; 95%CI, 0.97-0.99), and medication received from a mental health specialist (AOR, 2.91; 95%CI, 2.04-4.15). Decomposition analysis showed that the first 2 of these 4 factors were associated with only the conditional probability of an individual treatment professional being perceived as helpful (age at first depression treatment: AOR, 1.02; 95%CI, 1.01-1.02; educational level: low: AOR, 0.48; 95%CI, 0.33-0.70; low-average: AOR, 0.62; 95%CI, 0.44-0.89; high-average: AOR, 0.67; 95%CI, 0.49-0.91 vs high educational level), whereas the latter 2 factors were associated with only persistence (treatment delay: AOR, 0.98; 95%CI, 0.97-0.99; treatment type: AOR, 3.43; 95%CI, 2.51-4.70). CONCLUSIONS AND RELEVANCE The probability that patients with MDD obtain treatment that they consider helpful might increase, perhaps markedly, if they persisted in help-seeking after unhelpful treatments with up to 9 prior professionals.